Microbiological and physicochemical characterization of probiotic fermented milk throughout the shelf life under different storage temperatures - Lacerda, Sthefany [UNESP]; Santos, Marcos Cruz do [UNESP]; Martins, Otávio Augusto [UNESP]; Pereira, Juliano Gonçalves [UNESP] (FapUNIFESP (SciELO), 2022)
Probiotics can be defined as viable or inviable microbial cell (vegetative/spore or intact/ruptured) that is potentially healthful to the host. Commonly linked to fermented milk, one of the most popular fermented beverage, due to the greater consumer acceptance of dairy products. However, technical aspects such as inappropriate storage conditions and transport facilities can influence the viability of the microorganisms in these products. Therefore, the aim of this study was to evaluate the microbiological and physicochemical quality of probiotic fermented milk sold in the city of Botucatu/SP during its shelf life, and to determine the effect of different storage temperatures (4 °C and 12 °C), comparing results with the standard limits. For this purpose, four brands of probiotic fermented milk (A, B, C, and D) were analyzed counting lactic acid bacteria and evaluating physicochemical parameters (pH, acidity, proteins, lipids, moisture, and ash). As a result, only brand D did not fit the parameters determined by the technical norms of the Brazilian legislation; the variation in storage temperature, did not show significant influence on the results of the tested parameters.
Keywords: fermentation; food safety; functional foods; quality control